Anthropological Discourse within Los Pasos Perdidos: Contact Zones and Myth-Making in the Latin American Travel Narrative - Cervantes-Gómez, Magdalena
Since the time of its discovery, Latin America has been subjected to scrutiny, study, and documentation. Beginning with Columbus' writings, European vision of Latin America has been inextricably tied to the written word, thus creating the beginnings of the Latin American mythos and the antecedent to the travel narratives. According to Roberto González Echevarría, Alejo Carpentier's Los Pasos Perdidos "is a turning point in the history of Latin American narrative, the founding archival fiction." However, much of the scholarship has moved away from the fundamental thematic of ethnographic writing within the novel. As this paper argues, the ethnographic underpinning that Carpentier sets forth through the protagonist-narrator's encounter with a cultural "other" is crucial in understanding how the text situates Latin America within the ambit of literary fiction, as well as within the anthropological discourse it emulates. Drawing largely from the works of James Clifford and Mary Louise Pratt, this paper examines Los Pasos Perdidos as an archetype of the European myth-building of Latin America as it revisits the underlying anthropological discourse of the novel through the concept of the contact zone. In doing so, this article questions the space Carpentier configures for Latin America within the intersection of anthropology and the travel writing that emerges from this region.